2012
DOI: 10.1177/1744629512455894
|View full text |Cite
|
Sign up to set email alerts
|

Changing day services

Abstract: Models of day services for people with intellectual disabilities in Scotland are changing, with the purpose, content and availability being reviewed. There has been concern that a move to more flexible 'alternative day opportunities' is driven more by reduced budgets than a policy of modernising day services in response to individual needs. During a day services review, a questionnaire was used to rate and to collect views on existing services from 60 carers, service users and staff. This included evaluating d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…As a result, relationships and friendships tend to develop only within particular settings and remain bound to those settings. Similarly, Campbell (2012) reporting research carried out in Scotland points out that one of the most valued aspects of day centres is friendship, while Cramm et al (2009) in their study based in the Netherlands report that people with intellectual disability who are in employment consider it important for co-workers to be friendly. One of the participants in the study by Welsby and Horsfall (2011) even mentions going to work as the only means of seeing her friends.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, relationships and friendships tend to develop only within particular settings and remain bound to those settings. Similarly, Campbell (2012) reporting research carried out in Scotland points out that one of the most valued aspects of day centres is friendship, while Cramm et al (2009) in their study based in the Netherlands report that people with intellectual disability who are in employment consider it important for co-workers to be friendly. One of the participants in the study by Welsby and Horsfall (2011) even mentions going to work as the only means of seeing her friends.…”
Section: Introductionmentioning
confidence: 99%
“…6. These difficulties for people with intellectual disabilities to obtain paid work are internationally recognized (Campbell 2012;Lövgren, Markström, and Sauer 2013;McGlinchey et al 2013). 7.…”
Section: Discussionmentioning
confidence: 99%
“…Using longitudinal data over the period 2004-2012, Hultkrantz, Värja, and Larsson Tholén (2016 analysed economic and political determinants of the Swedish municipalities' expenditure per user for day activities (DAs henceforth). It was found that the intended equality of the quality of these services independent of location has not been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…They were intended to provide parents or other family carers with a break while keeping their relatives safe in a caring environment (Fleming, McGilloway, & Barry, 2017). Over time, the supports have also evolved to meet the needs of the people with intellectual disabilities through the provision of training, educational, and leisure pursuits (Whittaker & McIntosh, 2000;Cole & Williams, 2007), although the provision of breaks for family carers remained an equal if not more important function of day services (Campbell, 2012).…”
Section: The Evolution Of Day Services In Irelandmentioning
confidence: 99%